A low-noise current-sensitive preamplifier for X-ray computed tomography with applying a charge-sensitive preamplifier. Issue 1 (2nd January 2021) - Kanno, Ikuo; Onabe, Hideaki
ABSTRACT: A low-noise current-sensitive preamplifier was developed for aiming low-dose X-ray computed tomography with applying a charge-sensitive preamplifier. We compared the number of X-ray photons needed for current measurement with the new preamplifier with that needed with a conventional preamplifier. Also, the dose rates for above conditions were measured by a commercial dose rate meter. Results show that the new preamplifier reduced the number of X-ray photons needed by two orders of magnitude compared with the conventional one.